2018
DOI: 10.1101/462911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of oral microbiota in marmosets: feasibility of using the marmoset as a human oral disease model

Abstract: 299/300) 2 As the world's population is aging, there is an increasing demand for research 3 regarding aging and aging-related disorders, to achieve better understanding of aging. Ideally, 4 such research would be performed with human subjects. However, due to ethical 5 considerations, animals such as rodents and monkeys are used as alternatives. Among 6 these alternative models, non-human primates are preferred because they share common 7 traits with humans. The small South American common marmoset (Callithr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Firstly, it extends the few studies focused on non-human oral and vaginal microbiota, and secondly, by examining wild rodents and those transferred to captivity, we confirmed that each microbiota responds differently to a changing environment. Our results could help in the detection of unique features in both oral and vaginal microbiota, groups that are often explored in relationship to different diseases 5 , 46 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Firstly, it extends the few studies focused on non-human oral and vaginal microbiota, and secondly, by examining wild rodents and those transferred to captivity, we confirmed that each microbiota responds differently to a changing environment. Our results could help in the detection of unique features in both oral and vaginal microbiota, groups that are often explored in relationship to different diseases 5 , 46 .…”
Section: Discussionmentioning
confidence: 91%
“…While several recent studies have characterized oral or vaginal microbiota in captive mammals 44 46 , these communities are rarely scrutinized in wild populations. As such, our findings extend those of the only existing study on oral microbiota in a free-living murine species (the house mouse Mus musculus musculus 47 ), for which dominance of Pasteurellaceae of the phylum Proteobacteria (> 75%) was reported.…”
Section: Discussionmentioning
confidence: 99%